Destination Choice Through Push And Pull Motivations Factors Of Vietnamese Domestic Tourists - Nhu Ngoc, Ho (2024)
This study investigates the destination choices of Vietnamese domestic tourists through the lens of push and pull motivational factors. The objectives are to identify the underlying travel motivations perceived by Vietnamese domestic tourists, examine the push and pull motivational factors, and compare the important of push and pull motivational factors on destination choices across destinations. A quantitative approach was employed. Descriptive analysis, factor analysis, and binary logistic regression models were applied. The findings resulted from descriptive analysis revealed the six push motivational items that pushed Vietnamese domestic tourists and five pull motivational items that pulled them to specific destinations. Additionally, the study identified seven push and four pull motivational factors from the findings resulted from factor analysis. Based on the results from binary logistic regression it found that while push motivational dimensions did not differ significantly across destinations, pull motivations dimensions varied. Various pull dimensions influenced the choice of different destinations. The study contributes to both practical implications and academic literature. Academically, it enriches the understanding of tourist behaviour and destination choice, particularly in the context of Vietnam, and provides a framework for future research in tourism studies. Practically, it offers insights for tourism stakeholders to tailor marketing strategies and develop tourism policies that align with the motivations of Vietnamese domestic tourists. Several implications based the findings of this study provided tourism authorities to create tourism policies.